Virtual corporate memory: knowledge management implementation for academic environment of institutions higher learning / Wan Nor Hannani Wan Dagang - Wan Dagang, Wan Nor Hannani (2014)
Rapid advances in technologies are fostering globalization of information. Information system nowadays has been extended to Knowledge Management System (KMS) focusing on knowledge as main contents instead of information. Knowledge in organization, supported by appropriate technology will produce organizational memories that provide necessary support for organization to learn and grow. As a beginning, organizations need to review their knowledge to learn from successes or failure. Although it may be easier to learn from failure, organizations should have a mechanism to retain what was done correctly as well as what was not. Such mechanism is typically referred to as a Corporate Memory (CM). Hence, this research intends to gather information on how is the knowledge retention in an organization and proposed Virtual Corporate Memory (VCM) model with scope focuses on academic environmental of Institutions Higher Learning (IHL). IHL having problem in managing their valuable knowledge in term of knowledge is scattered and some knowledge belong to individuals whom reluctant to share. This problem is the foundation of the study. This qualitative interpretive research is based on the purposive method in order to gather data through the interviews with administrators of Information Technology (IT) department in one of the Institution of Higher Learning (IHL) in Malaysia. Then, the conceptual analysis is used to structure the data from the interviews. Finally, the proposed model of CM implementation which consists of three main components which is people, organization process and technology supported by other elements such as planning, content of the knowledge, support from senior expertise or legacy system, the knowledge access and also tools and systems to retain the corporate memory of the institutions has being identified. This model is developed based on current implementation model and literature review that researcher has gone through. This research contributes on modelling the VCM model for academic environmental of IHL besides discovering the indirectly relationship between knowledge management and corporate memory.